Primary closure versus T-tube drainage after laparoscopic choledocholithotomy: a prospective randomized study - Shakya, Jugendra Pal Singh; Agrawal, Neelabh; Kumar, Arun; Agrawal, Archana; Singh, Akash; Singh, Kunwar Vishal; Yadav, Charu (International Surgery Journal, 2017)
Background: Traditionally laparoscopic common bile duct exploration is followed by T-tube placement because of which patients suffer problems related to T-tube thereby increasing the morbidity of patients. Primary closure of CBD following laparoscopic choledocholithotomy is now being considered as an alternative superior to the traditional method. This study is designed to analyse the outcome of primary CBD repair in terms of mean operation time, duration of hospital stay and post-operative morbidity. Methods: A prospective randomized study was done in which 40 patients at our institute and associated hospitals were divided into two groups to compare the results of primary closure to T-tube placement following laparoscopic choledocholithotomy. Results: 40 patients were included in this study. The mean operating time was observed to be 65±14.05 mins in Group A (primary closure) patients while that in case of Group B (T-tube drainage) patients was 95.25±9.66 mins with a p-value 0.0001 which is considered statistically significant. The average duration of hospital stay in Group A (primary closure) was 8.2 days which was much shorter than that of Group B (T-tube drainage) patients which was of 15.7 days. The post-operative complication was observed in 1 patient of Group A (primary closure) while post-operative complication occurred in 3 patients of Group B (T-tube drainage). Conclusions: This study indicates that primary repair following laparoscopic choledocholithotomy is a safer and more effective method than T-tube drainage and we strongly recommend this procedure in clinical practice.